Exploring the effects of skeletal architecture and muscle properties on bipedal standing in the common chimpanzee (Pan troglodytes) from the perspective of biomechanics - Xv, Xiao-Wei; Chen, Wen-Bin; Xiong, Cai-Hua; Huang, Bo; Cheng, Long-Fei; Sun, Bai-Yang (Frontiers in Bioengineering and Biotechnology, 2023)
The common chimpanzee, as both the closest living relative to humans and a facultative bipedal, has the capability of bipedal standing but cannot do so fully upright. Accordingly, they have been significant in elucidating the evolution of human bipedalism. There are reasons why chimpanzees can only stand with their hips–knees bent, such as the distally oriented long ischial tubercle and the almost absent lumbar lordosis. However, how the relative positions of their shoulder–hip–knee–ankle joints are coordinated is unknown. Similarly, the biomechanical distribution of muscles and what affects the erectness of standing and the muscle fatigue of the lower limbs remain a mystery. The answers will light up the evolutional mechanism of hominin bipedality, but these conundrums haven't been shed much light upon, because few studies have comprehensively explored the effects of skeletal architecture and muscle properties on bipedal standing in chimpanzees. Thus, we first built a musculoskeletal model comprising the head-arms-trunk, thighs, shanks, and feet segments of the chimpanzee, and then, the mechanical relationships of the Hill-type muscle-tendon units (MTU) in bipedal standing were deduced. Thereafter, the equilibrium constraints were established, and a constrained optimization problem was formulated where the objective was defined. Finally, simulations of bipedal standing experiments were performed to determine the optimal posture and its corresponding MTU parameters including muscle lengths, activation, and forces. Moreover, to quantify the relationship among the parameters from all experimental simulation outcomes, the correlation analysis was employed. Our results demonstrate that pursuing the optimal bipedal standing posture, chimpanzees cannot simultaneously achieve maximum erectness and minimum muscle fatigue of the lower limbs. For uni-articular MTUs, the relationship between muscle activation, relative muscle lengths, together with relative muscle forces, and the corresponding joint angle is generally negatively correlated for extensors and positively correlated for flexors. For bi-articular MTUs, the relationship between muscle activation, coupled with relative muscle forces, and the corresponding joint angles does not show the same pattern as in the uni-articular MTUs. The results bridge the gap between skeletal architecture, along with muscle properties, and biomechanical performance of chimpanzees during bipedal standing, which advances the comprehension of bipedal evolution in humans.